(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The sedimentology and depositional architecture of the sequences cropping out in the towns of La Jaula and Agua del Médano, both in the Province of Mendoza, were analyzed with the purpose of reporting Late Miocene pedemont dunes in Cordillera Principal.